2022
DOI: 10.1021/acsanm.2c04315
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Functionalized with Imidazole Derivatives as Nanotransducers for Electrochemically Detecting Isothiazolinone Biocides

Abstract: Isothiazolinones, which are widely used as chemical additives in many industries, may lead to skin irritation and allergies, thereby adversely influencing human health and the environment. Therefore, this paper proposes an efficient strategy for screening nanohybrid transducers to selectively detect 2-octyl-3-isothiazolinone (OIT) as a representative isothiazolinone. Chemical receptor (CR) candidates consisting of two parts: a reactive imidazole unit and side functional group for covalent conjugation with grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The geometry was optimized using the B3LYP functional combined with the 6-31G(d) split-valence basis set. [31,32]…”
Section: Density Functional Theory Calculationsmentioning
confidence: 99%
“…The geometry was optimized using the B3LYP functional combined with the 6-31G(d) split-valence basis set. [31,32]…”
Section: Density Functional Theory Calculationsmentioning
confidence: 99%
“…To effectively eliminate interlayer interaction, heteroatoms or functional groups have been introduced into 2D materials via various chemical means, such as oxidation/reduction, selective etching, and specific addition reactions (diazonium, nitrene, carbene, etc. ). ,, In particular, diazonium chemistry has been widely used for graphene, MoS 2 , WS 2 , WSe 2 , Sb 2 S 3 , and Bi 2 S 3 . ,, Strano and co-workers provided a comprehensive summary of studies on the covalent functionalization of graphene with diazonium compounds. , The grafting of diazonium compounds onto graphene was dependent on graphene’s Fermi energy and the density of states of the diazonium reactants, and therefore the resulting reaction rate was highly affected by the number of graphene layers, edge states, defects, and the electrostatic environment. One example is an edge-functional MoS 2 exfoliation method that employs a soft organic compound as an exfoliating agent with no metallic or organometallic components .…”
Section: Scalable Fabrication Processmentioning
confidence: 99%
“…A range of 2D materials with promising properties, such as transition metal dichalcogenides (TMDs), transition metal oxides (TMOs), and transition metal carbides/nitrides (MXenes), has emerged, with a strong potential for widespread application in a variety of fields. Many studies on 2D materials have shown that they have extraordinary catalytic and electronic properties. TMDs, ,,,, for example, have been utilized as cocatalysts for enhanced photocatalysis due to the highly active chalcogenide atoms at the exposed edges and a suitable band position. In particular, the process of reducing bulk 2D materials into single or a few layers involves inevitably the severing of their two-dimensionally oriented chemical bonds.…”
Section: Introductionmentioning
confidence: 99%
“…125,126 Graphene exhibits extraordinary properties such as a large surface area (B2600 m 2 g À1 ), excellent mechanical strength, high thermal and electrical conductivity (B5000 W m À1 K À1 ), high carrier mobility (2 Â 10 5 cm 2 V À1 s À1 ), and optical transparency. [127][128][129][130] Because of its exceptional electrical conductivity, graphene is an ideal material for high-performance electronic applications, including energy storage and conversion devices as well as sensors that require fast charge transport. [131][132][133] The efficient electron transfer and tunable electronic properties of graphene play an important role in catalyzing various chemical reactions, particularly for water splitting.…”
Section: Graphenementioning
confidence: 99%